Coefficient Estimate of Biunivalent Functions of Complex Order Associated with the Hohlov Operator. (10th April 2014) - Peng, Z.; Murugusundaramoorthy, G.; Janani, T.
Abstract : We introduce and investigate a new subclass of the function classΣ of biunivalent functions of complex order defined in the open unit disk, which are associated with the Hohlov operator, satisfying subordinate conditions. Furthermore, we find estimates on the Taylor-Maclaurin coefficients| a 2 | and| a 3 | for functions in this new subclass. Several, known or new, consequences of the results are also pointed out.